2019
DOI: 10.1371/journal.pone.0223305
|View full text |Cite
|
Sign up to set email alerts
|

Trial registration as a safeguard against outcome reporting bias and spin? A case study of randomized controlled trials of acupuncture

Abstract: Background and objectiveTrial registration is widely endorsed as it is considered not only to enhance transparency and quality of reporting but also to help safeguard against outcome reporting bias and probably spin, known as specific reporting that could distort the interpretation of results thus mislead readers. We planned to investigate the current registration status of recently published randomized controlled trials (RCTs) of acupuncture, outcome reporting bias in the prospectively registered trials, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Registered clinical trials showing negative results (where the treatment tested showed no effect) are statistically less likely to be published, and even when published they usually take, on average, 1 year more to get released than trials with positive results. [20, 21]. It was also proven that statistically significant studies may be cited more than negative studies on the same topic, increasing the bias [22].…”
Section: Factors At Playmentioning
confidence: 99%
“…Registered clinical trials showing negative results (where the treatment tested showed no effect) are statistically less likely to be published, and even when published they usually take, on average, 1 year more to get released than trials with positive results. [20, 21]. It was also proven that statistically significant studies may be cited more than negative studies on the same topic, increasing the bias [22].…”
Section: Factors At Playmentioning
confidence: 99%
“…In fact, Anaesthesia only considers for publication trials that have been registered. Perhaps the majority of trials from these seven countries were not even registered [7,8] (with variability in the registration rates across countries and over time). Moreover, the proportion of false and zombie trials may be higher among studies that don't even bother to register themselves than among registered ones.…”
Section: Data Originmentioning
confidence: 99%
“…The results of several recently published studies, affected by reporting bias, suffered from a reduction in their strength of evidence [14]. However, only a limited number of studies have investigated the current registration status of published randomized controlled trials (RCTs) related to acupuncture-moxibustion as outcome reporting bias in prospectively registered trials [15, 16]. These studies only included RCTs and registered studies that were given a “completed” status in registries.…”
Section: Introductionmentioning
confidence: 99%